Development of A 5.4 Ghz C-Band Microstrip SAR Antenna for A Tsunami Detector - Chaniago, Erik; Haidi, Junas; Santosa, Hendy (Indonesian Journal of Aerospace, 2022)
A Tsunami is a series of massive oceanic waves resulting from profound tectonic activities in the seabed. The disaster's devastating effect makes fast information delivery during a tsunami crucial in minimizing losses. For this reason, Tsunami warning systems need to be supported by a rapid detection technology. In recent years, radar has been implemented as a tsunami detector due to its sensitivity to oceanic waves. An array antenna using advanced microstrip technology, as the main component of a radar system, can fulfill the requirement for tsunami rapid detection. This paper presents the work that we conducted to develop a tsunami detection antenna using the array approach to improve gain and optimize radiation patterns. We designed a patch antenna with 12 mm in length and 21 mm in width and performed some simulations to obtain the antenna parameters such as gain, bandwidth, and optimal radiation patterns. As the results of our investigation, we determined the resonance frequency to be 5.4 GHz. The study produced a gain of 9.07 dB through simulations on an antenna that resonates at a frequency that meets the antenna work criteria, which include a loss of -26.69 dB, a VSWR of 1.09, and an HPBW (Half Power Beamwith) of 17.3°. Those values indicate that the antenna designed for tsunami detector applications functions correctly.